PENGARUH BRAND IMAGE DAN PRICE IMAGE TERHADAP PURCHASE INTENTION DENGAN STORE IMAGE SEBAGAI VARIABEL INTERVENING PADA IBOX STORE DI WORLD TRADE CENTER (WTC) DI SURABAYA - Lenarto, Stefan; Putra, A.Y. Yan Wellyan Toni; Rahmawati, Veronika (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2017)
Increased buying interest in consumers is an activity to win the competition within the retail industry. There are several factors that can affect the intention of buying or purchase intention consumers. These factors are Store Image, Brand Image, Price Image. Where Brand Image and Price Image indirectly affect Purchase Intention but through Store Image, while Store Image directly influence Purchase Intention. Other variables that affect the Store Image directly are Brand Image and Price Image. This study aims to determine the effect of Brand Image and Price Image on Purchase Intention through Store Image. This research uses Structural Equation Modeling (SEM) analysis technique. The object of this research is consumer from IBOX Store at World Trade Center (WTC) Surabaya, with 154 respondents. The results of this study can be concluded: (1) Brand Image has a positive effect on Store Image, (2) Price Image has a positive effect on Store Image, (3) Store Image has positive effect on Purchase Intention, (4) Brand Image has positive effect on Purchase Intention through Store Image, (5) Price Image positively affects Purchase Intention through Store Image